Preselection of high and low ovulatory responders in sheep multiple ovulation and embryo transfer programs - Bruno Galarraga, Maria Macarena; Cueto, Marcela Isabel; Gibbons, Alejandro Eduardo; Pereyra Bonnet, Federico; Subiabre, Marcos Sebastian; González-Bulnes, Antonio (2017)
The present study evaluated the feasibility of carrying out an easy-to-handle and cost-efficient test for the preselection of high– and low–ovulatory responder ewes under superovulatory protocols. The test was based on the assessment of the number of ovulations obtained in response to the administration of a single-shot eCG treatment. The predictive value of the test was determined by comparing the number of ovulations with yields obtained in response to a multiple-dose FSH treatment. In addition, the study determined possible effects of follicular status at first FSH dose and their relationship with subsequent ovarian response. A total of 31 Merino ewes received hormonal treatment comprising the administration of 800 IU of eCG at the end of progestative treatment. Twenty-three days later, multiple-dose FSH treatment (80-mg FSH, in six decreasing doses between Days 12 and 14 of a second progestative treatment) was applied to the same ewes. The study showed a significant relationship between the number of corpora lutea obtained in response to eCG treatment with respect to those obtained in response to FSH treatment (r = 0.791; P < 0.05), which resulted in 84% recurrence rate. The number of embryos was greater for high-responder in relation to low-responder ewes (7.2 ± 3.7 and 4.0 ± 3.9, respectively; P < 0.05), whereas rates of recovery and fertilization were similar between groups (P > 0.05). Hence, there was a tendency for a higher mean of grades 1 and 2 embryos in high-responder in relation to low-responder ewes (6.1 ± 3.8 and 3.7 ± 4.0, respectively; P < 0.1). No significant relationship was found between the number of corpora lutea in response to FSH treatment and the number of small and total follicles at first FSH dose (P > 0.05). However, a negative low relationship was found between the presence of large follicles and the ovulation rate in response to FSH treatment (r = −0.361; P < 0.05). In conclusion, the results show the feasibility of carrying out an easy-to-handle and cost-efficient procedure for the preselection of embryo donors. The procedure was based on high recurrence rate between hormonal treatments, which in turn accounts for a distinctive ewe ovulatory response.